3x - 2y=7 x =1
Substituting for x = 1 in your equation, we get
3 * 1 - 2y = 7
3 - 2y = 7
-2y = 7 -3
-2y = 4
-y = 4/2
- y = 2
y = -2
2006-12-27 06:41:00
·
answer #1
·
answered by pkababa 4
·
2⤊
0⤋
If x = 1, then 3(1) - 2y = 7 so that rearranging
-2y = 7 - 3 = 4
y = 4/(-2) = -2
2006-12-27 14:41:03
·
answer #2
·
answered by kellenraid 6
·
2⤊
0⤋
Put the 1 in for x:
3(1) - 2y = 7
3 - 2y = 7
Subtract 3 from both sides:
-2y = 4
Divide both sides by -2:
y = -2
2006-12-27 14:41:05
·
answer #3
·
answered by Joy M 7
·
2⤊
0⤋
you substitute the value for x into the equation. that gives you:
3(1)-2y=7. That gives you:
3-2y=7. You get y alone so you subtract three from both sides.
-2y=4. you divide both sides by -2.
Then you get y=-2
2006-12-27 15:27:00
·
answer #4
·
answered by blah 4
·
0⤊
0⤋
3x - 2y = 7
x = 1
Therefore; (3 x 1) - 2y = 7 (by substituting x = 1 into equation)
So; 3 - 2y = 7
2y = -4
y = -2
2006-12-27 15:14:09
·
answer #5
·
answered by Steve 2
·
1⤊
0⤋
substitute 1 for x:
3(1) - 2y = 7
3 - 2y = 7
subtract both sides by 3
3 - 3 - 2y = 7 - 3
-2y = 4
Divide both sides by -2
-2y/2 = 4/-2
y = -2
2006-12-27 14:41:51
·
answer #6
·
answered by jard jard binx 3
·
2⤊
0⤋
3x-2y=7; x=1
3*1-2y=7
3-2y=7
-2y=4
y=-2
2006-12-27 15:39:04
·
answer #7
·
answered by yupchagee 7
·
0⤊
0⤋
3x-2y=7; x=1
3(1)-2y=7
3-2y=7 [subtract 3 from both sides]
-2y=4 [divide both sides by -2]
y=-2
2006-12-27 14:49:05
·
answer #8
·
answered by Rebekah 2
·
1⤊
0⤋
SUB X = 1 INTO THE EQUATION
3X - 2Y = 7
3(1) - 2Y = 7
ISOLATE Y
-2Y = 7 - 3 -> -2Y = 4
Y = 4/-2
Y= -2
2006-12-27 14:41:25
·
answer #9
·
answered by Cu Den 2
·
2⤊
0⤋
of course y=-2
because:
3*1-2y=7,
-2y=4
y=-2
2006-12-27 15:53:28
·
answer #10
·
answered by lukasz88 2
·
0⤊
0⤋